Buoyancy effects on turbulent heat transfer of supercritical CO2 in a vertical mini-tube based on continuous wall temperature measurements. (July 2017) - Xu, Rui-Na; Luo, Feng; Jiang, Pei-Xue
Highlights: Focus on the location where T f ( r ) =  T pc (pseudocritical temperature). Propose y + | T f ( r ) = T pc estimating the value of y + at the location of T f ( r ) =  T pc. When y + | T f ( r ) = T pc  < 5, heat transfer enhances upward and decreases downward due to buoyancy. y + | T f ( r ) = T pc  = 5 is the onset of heat transfer deterioration. Abstract: Convection heat transfer of supercritical pressure fluid is important in industrial applications such as supercritical power stations, the supercritical CO2 Brayton cycle, Carbon Capture Utilization and Storage, and the thermal protection for rocket thrusters. Previous research has confirmed that there are three heat transfer regions for convection heat transfer of supercritical pressure fluid flowing inside vertical tubes: normal heat transfer, heat transfer deterioration, and heat transfer enhancement. However, existing research still carries inconsistent results, especially regarding the onsets of heat transfer deterioration of supercritical pressure fluid flow in vertical tubes. Here we propose a new view, by estimating the location where local fluid temperature, T f ( r ) equals to the pseudocritical temperature, T pc, in the transversal section inside the tube, then analyzing the relationship between the location where T f ( r ) =  T pc and the turbulent boundary layers in the near wall region, to identify buoyancy effects on turbulent heat transfer. By taking advantage of infrared thermometry measurement to achieve continuous wall temperature, theoretical analysis was validated by experiments of supercritical pressure CO2 in a vertical mini-tube with inner diameter of 0.953 mm. The experiments were performed for a pressure of 7.6–9.5 MPa, inlet mass flux from 255 kg/m 2  s to 685 kg/m 2  s, and heat flux from 12 kW/m 2 to 63 kW/m 2 . It is found that in contrast with the previous results, when the value of y + at the location of T f ( r ) =  T pc, y + | T f ( r ) = T pc, less than 5, heat transfer enhances for upward and decreases for downward flow due to the buoyancy effect. With the heat flux increasing or mass flux decreasing, the buoyancy effect on the turbulent convection heat transfer characteristics of supercritical pressure fluid in a vertical heated tube is be featured as the following regimes: for the upward flow, from no-effect to slight enhancement, significant reduction, recovery and then enhancement; for the downward flow, from no-effect to slight weaken, and then enhancement. Moreover, the experimental results showed that y + | T f ( r ) = T pc  = 5 is where there is an onset of heat transfer deterioration for the upward flow in a vertical heated tube induced by buoyancy effects. The results presented provide a better understanding of the special features of the turbulent convection heat transfer of supercritical pressure fluids in mini channels.